Debt Equity Ratio (DER) Analysis in Conventional Banks in Indonesia - Dwilita, Handriyani (Action Research Literate, 2025)
This study aims to provide a descriptive overview of the Debt to Equity Ratio (DER) as an indicator of capital structure and leverage levels in conventional banks in Indonesia during the 2018–2024 period. Changes in global economic conditions, regulatory dynamics, and liquidity pressures and fund costs encourage the importance of evaluating the capital structure of national banks. DER is used as a measure of a bank's ability to balance its own debt and capital use, which has direct implications for risk, profitability, and financial stability. Using a descriptive research approach with secondary data from bank financial statements listed on the Indonesia Stock Exchange, this study processed the maximum, minimum, and average values of DER, as well as describing the pattern of leverage movements through annual charts. The results of the study show that in general, conventional Indonesian banks are in the healthy category with DER in the low to moderate range (0.03–13.42). Most banks consistently maintain DERs within safe limits, supported by strong capital and prudent risk management practices. The variation in the value of the DER such as a significant increase in BBTN or very low values in PNBN and BGTG reflects differences in funding strategies, capital pressures, and internal restructuring. These findings are in line with the international literature that confirms that an optimal capital structure strengthens banks' resilience to economic shocks. Overall, this study confirms that DER remains an important metric in assessing the leverage conditions, capital stability, and financial health of conventional banking in Indonesia.